2004
DOI: 10.1002/j.2161-0045.2004.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Self‐Efficacy Theory to Career Counseling: A Personal Perspective

Abstract: The author provides a brief overview ofA. Bandura's (1977Bandura's ( , 1997 self-efficacy theory, followed by a discussion of the value of this theory to career counselors, which includes particularly useful features of the concept of self-efficacy and suggestions for its application in career assessment and counseling, with a special focus o n group interventions.My interest in Albert Bandura's (1977Bandura's ( ,1997 self-efficacy theory began in 1980. At that time, I had begun a research program examining ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
28

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 36 publications
3
137
0
28
Order By: Relevance
“…Aycan (2004) reported that gender-role stereotyping and a lack of support influenced women's self-perceptions and ideals. Betz (2004) suggested that young women have historically experienced barriers in developing selfefficacy and their self-confidence and self-esteem diminish during their academic preparation. Women may also lack self-efficacy in male-dominated occupations because of the socialization process they experience (Clement, 1987;Pell, 1996).…”
Section: Gendered Career Expectations Within the Pipelinementioning
confidence: 99%
“…Aycan (2004) reported that gender-role stereotyping and a lack of support influenced women's self-perceptions and ideals. Betz (2004) suggested that young women have historically experienced barriers in developing selfefficacy and their self-confidence and self-esteem diminish during their academic preparation. Women may also lack self-efficacy in male-dominated occupations because of the socialization process they experience (Clement, 1987;Pell, 1996).…”
Section: Gendered Career Expectations Within the Pipelinementioning
confidence: 99%
“…Self-effi cacy leads to generation of expectations as to the result of an action taken (Bandura, 2001). The key role of such a conviction is also accepted by other researchers (Schwarzer, Jerusalem, 1992;Zimmerman, Bonner, Kovach, 2005;Łaguna, 2010;Caprara et al, 2004;Betz, 2004;Lent et al, 2005;Nasta, 2007). According to Bandura (2001), the measurement of self-effi cacy should be adapted to the area of psychological functioning subject to analysis.…”
Section: Donald Super's Life-career Rainbowmentioning
confidence: 93%
“…Hirschi (2011) indicates that having positive views of oneself can impact on career change through the development of a clear sense of one's career goals, identity and purpose. Betz (2004) highlights the importance of perceptions of confidence in career choice, showing that low self-efficacy may limit the range of career options an individual considers or the success with which career options are achieved. All participants demonstrated increased self-awareness, which is known to play a part in career decision making, and in career change (Patton & McMahon, 2006) and which has been shown to be interrelated with career confidence (Skorikov & Vondracek, 2011).…”
Section: Implications For Practicementioning
confidence: 99%